Գնագոյացման հիմնախնդիրները բնական մենաշնորհի պայմաններում - Միքայել Սողոմոնյան (ՀՀ ԳԱԱ հրատ.)
В статье анализируются механизмы ценообразования в условиях естественной монополии, уделяя особое внимание на методы ценообразования (7 методов), а также раскрываются положительные и отрицательные стороны этих методов. The article analyzes the mechanisms of pricing in natural monopoly conditions, paying particular attention to pricing methods (7 methods), and also reveals the positive and negative aspects of these methods.
Keywords: Social Sciences; Economic Theory; Finance